Tinjauan Hukum Pasal 302 UU MD3 Mengenai Rangkap Jabatan dan Penggunaan Anggaran Kelembagaan Oleh Anggota DPD RI yang Berstatus Ketua PKK dan DEKRANASDA di Daerah - Jefirstson Richset Riwukore; Yohanes Susanto; Fellyanus Habaora (Law Department, Sharia and Law Faculty., 2020)
The purpose of this research is to examine the dual position and budget used of the Regional Representative Council of Indonesia toward the status of position as Chairperson of the Family Welfare Movement and the Chairperson of the National Craft Council in an area based on the provisions of the law. This study was carried out in Kota Kupang for 6 (six) months, from January to July 2019. This study was included in the case study classification. The subjects used were legal references and expert opinions. The type of data used is secondary data with documentation techniques. Analysis of the data obtained was done descriptively. The result of the analysis about concurrent of positions and budget used for DPD RI members in accordance with Article 302 paragraph (1) and paragraph (2) in Law in MD3 are not valid if someone other than being a DPD RI member is also as Chairperson of the Family Welfare Movement, and Chairperson of the National Craft Council.